Anion-mediated synthesis of monodisperse silver nanoparticles useful for screen printing of high-conductivity patterns on flexible substrates for printed electronics1. Issue 13 (14th February 2015) - Liu, Li; Wan, Xiaoxia; Sun, Lingling; Yang, Shuanglei; Dai, Zhigao; Tian, Qingyong; Lei, Mei; Xiao, Xiangheng; Jiang, Changzhong; Wu, Wei
<x xml:space="preserve">Abstract</x> Monodisperse silver nanoparticles (NPs) have been synthesized on a large scale by oxidation–reduction reactions in water and used in the printed electronics.